2007
DOI: 10.1211/jpp.59.1.0015
|View full text |Cite
|
Sign up to set email alerts
|

The protective action of scutellarin against immunological liver injury induced by concanavalin A and its effect on pro-inflammatory cytokines in mice

Abstract: Scutellarin is a natural compound from a Chinese herb. The purpose of this paper was to study the protective effect of scutellarin on concanavalin A (Con A)-induced immunological liver injury and its effect on liver nuclear factor kappaB (NF-kappaB), tumor necrosis factor alpha (TNF-alpha), interferon gamma (IFN-gamma), and inducible nitric oxide synthase (iNOS) expression in mice. Mouse liver injury was produced by injection of Con A 25 mg kg-1 via the tail vein. Scutellarin 50 or 100 mg kg-1 was peritoneally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Meanwhile, various studies have demonstrated that scutellarin protects liver cells from oxidative damage and inflammatory injury (Chen et al, 2013;Guo et al, 2013;Liu et al, 2003;Tan et al, 2010;. In addition, scutellarin has been reported to attenuate concanavalinA-, selenium-, and brain ischemia/reperfusion−induced liver injury (Eltayeb et al, 2004;Tan et al, 2007;Yang et al, 2003).…”
Section: Combination With Scutellaria Barbatamentioning
confidence: 99%
“…Meanwhile, various studies have demonstrated that scutellarin protects liver cells from oxidative damage and inflammatory injury (Chen et al, 2013;Guo et al, 2013;Liu et al, 2003;Tan et al, 2010;. In addition, scutellarin has been reported to attenuate concanavalinA-, selenium-, and brain ischemia/reperfusion−induced liver injury (Eltayeb et al, 2004;Tan et al, 2007;Yang et al, 2003).…”
Section: Combination With Scutellaria Barbatamentioning
confidence: 99%
“…Meanwhile, there are various reports which demonstrate that SC exerts well protection against oxidative damage and inflammatory injury (Liu et al, 2003;Tan et al, 2010;Chen et al, 2013;Guo et al, 2013). In addition, SC was reported to attenuate concanavalin A-, selenium-, and brain ischemia/reperfusion-induced liver injury Eltayeb et al, 2004;Tan et al, 2007). Thus, whether SC will protect against the hepatotoxicity induced by DB attracts our attention.…”
Section: Introductionmentioning
confidence: 99%
“…Scutellarin produces an anti-inflammatory effect via actions on arachidonic acid metabolism [6] . The compound has also been shown to have some anti-HIV effects [7] and to attenuate hepatocellular damage [8] . It is interesting that scutellarin exhibits weak estrogenic properties [9,10] , similar to genistein and apigenin.…”
Section: Introductionmentioning
confidence: 99%